Electronic cigarettes for smoking cessation - Hartmann-Boyce, J; McRobbie, H; Butler, AR; Lindson, N; Bullen, C; Begh, R; Theodoulou, A; Notley, C; Rigotti, NA; Turner, T; Fanshawe, TR; Hajek, P (Cochrane Collaboration, 2021)
Background Electronic cigarettes (ECs) are handheld electronic vaping devices which produce an aerosol formed by heating an e‐liquid. Some people who smoke use ECs to stop or reduce smoking, but some organizations, advocacy groups and policymakers have discouraged this, citing lack of evidence of efficacy and safety. People who smoke, healthcare providers and regulators want to know if ECs can help people quit and if they are safe to use for this purpose. This is an update conducted as part of a living systematic review.